2010
DOI: 10.1309/ajcpk6sbe0xoodhb
|View full text |Cite
|
Sign up to set email alerts
|

PCR Assays Detect B-Lymphocyte Clonality in Formalin-Fixed, Paraffin-Embedded Specimens of Classical Hodgkin Lymphoma Without Microdissection

Abstract: Hodgkin lymphoma (HL) was shown to be a B cell malignancy using PCR-clonality studies of microdissected Reed-Sternberg cells. While methods for the detection of B cell clonality could aid in the diagnosis of HL, microdissection is not practical in most clinical settings. We assessed the standardized BIOMED-2 IGH and IGK PCR primers for the detection of clonality using 50 consecutively diagnosed formalin-fixed paraffin-embedded (FFPE) classic Hodgkin lymphoma specimens. Without microdissection, clonality was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 11 publications
6
23
1
1
Order By: Relevance
“…PCR primer sequences for IGH variable gene framework region 3 analysis was designed as reported previously, and PCR was used to assess clonality using the BIOMED‐2 system . PCR master mixes were purchased from Invivoscribe Technologies (San Diego, CA), and PCR was performed as per the manufacturer's instructions using HotStart Taq DNA polymerase (Qiagen, Valencia, CA) …”
Section: Methodsmentioning
confidence: 99%
“…PCR primer sequences for IGH variable gene framework region 3 analysis was designed as reported previously, and PCR was used to assess clonality using the BIOMED‐2 system . PCR master mixes were purchased from Invivoscribe Technologies (San Diego, CA), and PCR was performed as per the manufacturer's instructions using HotStart Taq DNA polymerase (Qiagen, Valencia, CA) …”
Section: Methodsmentioning
confidence: 99%
“…An earlier study published in this journal [70] was confirmed by Burack et al [71] who show that without micro dissection HL samples have often a detectable clonal B-cell population (23/47); using primers for the Kappadeleting element locus is more sensitive than using those for the framework regions.…”
Section: Ancillary Techniquesmentioning
confidence: 81%
“…The sensitivity for detecting clonality in classical Hodgkin lymphoma (cHL) was the lowest (45%) in our study, probably due to the scarcity of tumor cells residing in an abundant admixture of non-malignant cells of different types that produces a polyclonal background signal and due to a high rate of somatic mutations in V regions 1,[44][45][46][47] . 39,45,50 ). In the group of T-cell lymphomas, the most successful detection of the PCR amplification was achieved for ALK + anaplastic large cell lymphoma (ALCL, 84.6%) and then for unspecified peripheral T-cell lymphoma (PTCLU, 83.6%).…”
Section: Discussionmentioning
confidence: 99%